A New Look at Suprasegmentals - Frodden, Cristina; McNulty, Maria (Íkala, Revista de Lenguaje y Cultura, 1996)
The communicative method has been criticized because in stressing the negotiation of meaning and the speakers intentions, accuracy has become a minor goal. Accuracy implies attention to form, for example, correct grammar and correct style, vocabulary and pronunciation It is true that we can communicate even though we make these kinds of errors, however, too many mistakes may hinder comprehension. Good pronunciation should be a goal in any course that attempts at communicating effectively. Kenworthy is right when she states that "a person may eventually understand what someone has said, but if this has involved too much frustration and irritation resulting from constant repetitions, rephrasings, or checks on what has been said (i.e. too much pain') then the communication cannot be described as efficient" (1992,16).